2012
DOI: 10.1016/j.pecs.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized bed waste incinerators: Design, operational and environmental issues

Abstract: The paper starts by reviewing the increasing production of waste and the growing importance of its thermal treatment, which aims at volume reduction of the waste, at the destruction, capture, and concentration of hazardous substances, and at the recovery of energy (WtE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(87 citation statements)
references
References 145 publications
(286 reference statements)
1
84
0
2
Order By: Relevance
“…FA2 contains more non-metallic elements such as S, Cl; however, FA6 contains more metallic elements such as Al, Mg, and Fe. Among the mineral compositions, CaO is usually used as the additive for SO x removal in the incineration system (Bodénan and Deniard, 2003), and the addition of SiO 2 used as bed material in FBI (Saxena and Jotshi, 1994;van Caneghem et al, 2012) weakens the pore structure of the fly ash surface. The smaller particle, more crushed surface, and less micropores of FA2 are as shown in Fig.…”
Section: 14mentioning
confidence: 99%
“…FA2 contains more non-metallic elements such as S, Cl; however, FA6 contains more metallic elements such as Al, Mg, and Fe. Among the mineral compositions, CaO is usually used as the additive for SO x removal in the incineration system (Bodénan and Deniard, 2003), and the addition of SiO 2 used as bed material in FBI (Saxena and Jotshi, 1994;van Caneghem et al, 2012) weakens the pore structure of the fly ash surface. The smaller particle, more crushed surface, and less micropores of FA2 are as shown in Fig.…”
Section: 14mentioning
confidence: 99%
“…Since the treatments of co-contaminated soils are limited, it is widely agreed that multiple costly techniques are required (Khan et al 2004). A number of investigations have shown that thermal treatment (thermal desorption, incineration, pyrolysis, gasification, and vitrification) is one of the effective processes for complex substances remediation (González-Corrochano et al 2012;Qi et al 2014;Qin et al 2015;Taube et al 2008;Van Caneghem et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ZIEGLO have studied the heat transfer performance of liquid-solid two-phase flow and three-phase fluidized bed, assuming the liquid content is constant in the three-phase flow and two-phase flow systems by setting the example of glass particle and column Y-particle. Then the three-phase flow and two-phase flow heat transfer coefficient should be expressed by thermal resistance of fluidized bed [20][21][22][23][24]. The result is that the three-phase fluidized bed heat transfer coefficient and the corresponding liquid-solid two-phase fluidized bed heat transfer coefficient can be obtained by the following correlation formula: …”
Section: Three-phase Flow Heat Transfer Modelmentioning
confidence: 99%